Research strategies : finding your way through the information fog - Badke, William B., 1949- (Bloomington, IN : iUniverse, LLC, 2014)
With the information provided here, writing research papers does not have to be frustrating or boring. It is possible to develop significant skills in order to make the writing process much easier, and the author explains the skills and strategies you need to efficiently and effectively complete a research project . In this book, the author offers a clear, simple, roadmap for conducting research and navigating the vast new world of information and technology. He details the entire research paper process from start to finish, and provides insightful and helpful information.
Welcome to the information fog -- Taking charge -- Database searching with keywords and hierarchies -- Metadata and the power of controlled vocabularies -- Discovery searches, library catalogs and journal databases -- Internet research -- Other resources and case studies in research -- Learning how to read for research -- Organizing your resources to write your paper -- Tips on research writing -- Appendix 1 : A research paper clinic: more tips and troubleshooting for development of great research papers -- Appendix 2: This textbook and Information literacy competency standards for higher education (ACRL).
Includes index.
Keywords: Public services (Libraries) -- Handbooks, manuals, etc; Libraries and students -- Handbooks, manuals, etc; Bibliography -- Methodology -- Handbooks, manuals, etc; Research -- Methodology -- Handbooks, manuals, etc; Report writing -- Handbooks, manuals, etc; Database searching -- Handbooks, manuals, etc; Online bibliographic searching -- Handbooks, manuals, etc; Internet searching -- Handbooks, manuals, etc; Informatieverzameling; Literatuuronderzoek; Bibliography -- Methodology; Database searching; Internet searching; Libraries and students; Online bibliographic searching; Public services (Libraries); Report writing; Research -- Methodology; Information Retrieval; Recherche; Wissenschaftliches Arbeiten; Handbooks, manuals, etc